Local Community Adaptation to Flood Disaster In Soppeng District - Rusdi Rusdi; Feri Padli; Alonge Titus Adeyemi (JAMBURA GEO EDUCATION JOURNAL, 2023)
Every year floods occur in Soppeng regency. The high rainfall and land conversion become the main cause of the flood. It affects the society both in their life and their welfare. The community has carried out various responses and adaptation strategies to deal with the risk of future floods. Thus, this study aims to determine the local adaptation strategy of the community in dealing with flood disasters in Soppeng Regency. The method in this study was carried out using in-depth interviews and observations in flooded areas. The community participation comes from socially inductive research that produces descriptive results. The result of this research shows that the lack of coordination between the community, government, and private parties (NGOs) leads to higher vulnerability. In addition, the adaptation model carried out by the community begins at the household level, especially the house-building model in the form of a stilt house. It consists of two parts namely, the lower and the upper. The lower part is usually used to deviate goods, agricultural materials, and vehicles, while the upper part is used as a place to rest and carry out daily routines such as cooking, chatting with neighbors, receiving guests, and so on. The act of adaptation in groups is by raising the position of the house to the second floor, building a small embankment, and moving household appliances to a higher place.